2018
DOI: 10.1007/s40571-018-00219-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation of an elastoplastic contact model for spherical discrete elements

Abstract: A contact model for the normal interaction between elastoplastic spherical discrete elements has been investigated in the present paper. The Walton-Braun model with linear loading and unloading has been revisited. The main objectives of the research have been to validate the applicability of the linear loading and unloading models and estimate the loading and unloading stiffness parameters. The investigation has combined experimental tests and finite element simulations. Both experimental and numerical results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Both figures show the limitations of using a linear model for unloading stiffness, even when the gradients are independently calibrated for each material. The results shown in Fig..10 may be compared with the analytical and numerical findings of Rojek et al[23], which, conversely, show that the linear relation of Luding is appropriate. However, it should be noted that a hardening plasticity model was used in this study with only a single set of parameters.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Both figures show the limitations of using a linear model for unloading stiffness, even when the gradients are independently calibrated for each material. The results shown in Fig..10 may be compared with the analytical and numerical findings of Rojek et al[23], which, conversely, show that the linear relation of Luding is appropriate. However, it should be noted that a hardening plasticity model was used in this study with only a single set of parameters.…”
mentioning
confidence: 67%
“…Rathbone et al used finite element studies to establish the magnitude of an effective curvature for a Hertzian unloading response as a function of Poisson's ratio and displacement before unloading, for spheres subject to small deformations. Finite element studies were conducted by Rojek et al [23] to determine the unloading response of metal spheres, described by a powerlaw hardening plasticity model, for a wide range of displacements, concluding that the linear Walton-Braun relationship between dimensionless load and dimensionless displacement is sufficiently accurate, and that unloading stiffness (defined as maximum load before unloading divided by recovered displacement) has a linear dependence on dimensionless displacement. Recognising the importance of contact area development for particle load-displacement response, Vu-Quoc et al [24] developed an incremental algorithm for elastoplastic contact based on tracking the development of total and plastic contact area, which was calibrated using finite element simulations and shown to be accurate for small displacements.…”
Section: Introductionmentioning
confidence: 99%
“…The paddy mud studied in this paper has a high water content due to long-term soaking, and the adhesion between particles leads to complex and diverse mechanical behaviors of paddy mud. The Hertz-Mindlin with JKR cohesion contact model can better characterize the obvious adhesion and agglomeration between particles due to electrostatic force and water content, which is suitable for moisture-containing materials with significant bonding and agglomeration caused by moisture Rojek et al, 2019), as shown in Fig. 6.…”
Section: Mud Particles Contact Model Selectionmentioning
confidence: 99%
“…In this case, element-element interaction is traditionally modelled using harmonic interaction potentials (such an interaction is schematically represented by connecting the centers of the elements with two springs oriented in the central and tangential directions) [22,28,29]. Some models also use nonlinear (elastic-plastic or viscoelastic Maxwell type) formulations of pair-wise interaction forces F cp ik and F tp ik [30,31] for simulation of granular media and porous structures with non-linear/ductile rheological properties of the material of the skeleton walls or granules. However, such potentials make possible adequate description of the mechanical behavior of porous systems only at a "low" scale (the scale of discontinuities or granules).…”
Section: Introductionmentioning
confidence: 99%